Dietary Intervention with Chayote for Blood Pressure Control - Ismail, Andi Almeira Zocha; Ismail, Andi Regina Acacia; Yusram, Aliyyah; Jamilah, Sitti (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
High blood pressure is a major risk factor for heart-related conditions, such as stroke and heart attack. Dietary management is essential for regulating blood pressure, and foods high in potassium, like chayote (Sechium edule, Latin) (labu siam, Indonesian), are becoming recognized for their possible antihypertensive benefits. This research examines the effects of eating chayote on the control of blood pressure in people with hypertension. An experimental approach was employed, involving three participants with hypertension and a history of stroke. The participants ate chayote combined with oats as a substitute for rice every day for a week. Blood pressure readings were taken prior to and following the intervention to evaluate alterations in systolic and diastolic values. The results indicate a notable decrease in blood pressure. Typically, systolic pressure dropped by 15 mmHg (9.4%), whereas diastolic pressure fell by 10 mmHg (10.5%). These findings indicate that chayote aids in blood pressure control due to its elevated potassium levels, promoting sodium elimination and supporting electrolyte equilibrium. Moreover, its fiber and flavonoids promote heart health by lowering cholesterol levels and minimizing oxidative stress. Although the outcomes are favorable, this research is constrained by its limited sample size and brief duration. Future studies should include larger and more varied populations, longer intervention durations, and an examination of chayote’s bioactive compounds to gain a clearer understanding of its long-term impact on blood pressure control.